Optimizing Human Resource Data Digitalization Processes In Clinics Through Mobile-Based Application Using A Prototype Method - Mochamad Nandi Susila (Jurnal Ilmiah Multidisiplin, 2025)
This study aims to develop a mobile-based application to optimize the digitalization process of human resource data management in clinics. The existing manual system was found to be inefficient, prone to data loss, and time-consuming. By applying the prototype development method, this research successfully produced a mobile application that allows users to input, store, and retrieve employee data more accurately and efficiently. The application was designed with separate modules for doctors, nurses, and administrative staff, incorporating user-friendly interfaces and data validation features to minimize input errors. User testing and feedback revealed that the application enhanced the speed and accuracy of data processing, improved accessibility, and supported real-time data updates. The results suggest that mobile technology can play a significant role in transforming data management practices in small-scale healthcare institutions. This innovation is expected to serve as a model for future digital transformation efforts in similar settings.